2013
DOI: 10.1515/aot-2013-0002
|View full text |Cite
|
Sign up to set email alerts
|

Color sensitivity of the multi-exposure HDR imaging process

Abstract: Multi-exposure high dynamic range(HDR) imaging builds HDR radiance maps by stitching together different views of a same scene with varying exposures. Practically, this process involves converting raw sensor data into low dynamic range (LDR) images, estimate the camera response curves, and use them in order to recover the irradiance for every pixel. During the export, applying white balance settings and image stitching, which both have an influence on the color balance in the final image. In this paper, we use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The spectral responsivities originate from a database by Jiang et al (2013). The spectral responsivities of HDR images was considered identical to the camera's raw spectral responsivity (Lenseigne et al, 2013). Additionally, 205 SPDs, as illustrated in Figure 2, of light sources that are commercially available were collected , containing LEDs (117), fluorescents (35), incandescent (17), halogens (31), metal halides ( 4) and sodium pressure lamps (1) from 300 nm to 900 nm with steps of 0,5 nm originating from the LSPDD database by Roby and Aubé (2012).…”
Section: Methodsmentioning
confidence: 99%
“…The spectral responsivities originate from a database by Jiang et al (2013). The spectral responsivities of HDR images was considered identical to the camera's raw spectral responsivity (Lenseigne et al, 2013). Additionally, 205 SPDs, as illustrated in Figure 2, of light sources that are commercially available were collected , containing LEDs (117), fluorescents (35), incandescent (17), halogens (31), metal halides ( 4) and sodium pressure lamps (1) from 300 nm to 900 nm with steps of 0,5 nm originating from the LSPDD database by Roby and Aubé (2012).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Lenseigne et al . 22 showed that the spectral responsivity of the HDR has large similarities, including the effect of white balancing, to the raw spectral responsivity, indicating that the colour space of the HDR image is camera dependent and not necessarily similar to the spectral sRGB responsivity.…”
Section: Introductionmentioning
confidence: 99%